2015
DOI: 10.1515/hsz-2014-0284
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 suppresses non-small cell lung cancer growth by targeting JMJD2A

Abstract: Lung cancer has been the most prolific cancer in China - as in the rest of the world - with a high death rate and low 5-year survival rate. Previous evidence showed that JMJD2A is over-expressed in human non-small cell lung cancer (NSCLC) tissues compared to adjacent normal tissues, and that high level of JMJD2A predicts poor overall and disease-free survival. However, the mechanism by which JMJD2A is regulated in human NSCLC is not fully understood. In the present study, we identified that the SIRT2 as an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…More importantly, one study also showed that Sirt2 Ϫ/Ϫ mice formed tumors in multiple tissues and that the incidence of the tumors increased slowly with age (21). Previous studies also showed that SIRT2 was significantly downregulated in non-small cell lung cancer (23,25,56). Our study showed that HRD1 2CA mutant C291, 294A was used.…”
Section: Discussionsupporting
confidence: 57%
“…More importantly, one study also showed that Sirt2 Ϫ/Ϫ mice formed tumors in multiple tissues and that the incidence of the tumors increased slowly with age (21). Previous studies also showed that SIRT2 was significantly downregulated in non-small cell lung cancer (23,25,56). Our study showed that HRD1 2CA mutant C291, 294A was used.…”
Section: Discussionsupporting
confidence: 57%
“…However, little is known about how JMJD2A is regulated. One recent report showed that expression of JMJD2A is suppressed by tumor suppressor sirt2 [51]. Moreover, as mentioned above, the stability of JMJD2A is regulated by ubiquitination [11,13,39].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT2 acts as a tumor suppressor gene in human gliomas through the regulation of microtubule network [15]. SIRT2 suppresses non-small cell lung cancer growth by targeting JMJD2A [16]. SIRT2 inhibits non-small cell lung cancer cell growth through impairing Skp2-mediated p27 [17].…”
Section: Discussionmentioning
confidence: 99%